SEASONAL ABUNDANCE OF MILLIPEDES IN A MEDITERRANEAN OAK FOREST (SOUTHERN FRANCE) (ISRAEL JOURNAL OF ZOOLOGY, 1995)
The millipede community of a helm oak forest (Quercus ilex) in southern France was sampled seasonally for 2 yr, at two depths in the forest floor. Despite the strong seasonality of climatic conditions, both recruitment periods and vertical displacements in the soil change markedly according to species; contrasting examples are provided by Glomeris marginata, which breeds in summer and burrows in winter, and by Opisthocheiron elegans, which behaves the opposite way. At the community level, biomass changes significantly between a spring minimum and an autumn maximum. Such a pattern results from the high abundance of G. marginata, a drought-resisting species which grows and reproduces during summer but experiences substantial winter mortality. The seasonal pattern is different in number of individuals due to the minute litter-dweller Polyxenus lagurus, which has a low population density in early autumn. The biomass of macrosaprophagous millipedes on the site (annual mean of 10.5 g live weight m(-2); autumn peak of 14.6 g live weight m(-2)) is much higher than that recorded further north in Europe, and its significance for litter consumption in Mediterranean forest is discussed.